POSSIBILITIES AND RESULTS OF HARDNESS CONTROL OF CAST IRON CASTINGS BY MAGNETIC METHOD AFTER POLAR MAGNETIZATION - S. G. Sandomirskij; V. L. Tsukerman; L. Z. Pisarenko (Литьë и металлургия)
The correlation dependence between hardness of castings of high-duty cast irons and grey irons, contents of pearlite in metallic mould of high-duty cast iron and parameters CrH of remanent magnetic induction field over surface of castings after magnetization with constant magnet, is determined and analyzed